LARGE-SCALE FAILURES ON DOMES AND STRATOCONES SITUATED ON CALDERA RING FAULTS: SAND-BOX MODELING OF NATURAL EXAMPLES FROM KAMCHATKA, RUSSIA - Belousov A.; Walter T.R.; Troll V.R. (My University, 2005)
Edifices of stratocones and domes are oftensituated eccentrically above shallow silicic magmareservoirs. Evacuation of such reservoirs forms collapsecalderas commonly surrounded by remnants of one orseveral volcanic cones that appear variously affected anddestabilized. We studied morphologies of six calderas inKamchatka, Russia, with diameters of 4 to 12 km. Edi-fices affected by caldera subsidence have residual heightsof 250–800 m, and typical amphitheater-like depressionsopening toward the calderas. The amphitheaters closelyresemble horseshoe-shaped craters formed by large-scaleflank failures of volcanoes with development of debrisavalanches. Where caldera boundaries intersect suchcones, the caldera margins have notable outward em-bayments. We therefore hypothesize that in the process ofcaldera formation, these eccentrically situated edificeswere partly displaced and destabilized, causing large-scale landslides. The landslide masses are then trans-formed into debris avalanches and emplaced inside thedeveloping caldera basins. To test this hypothesis, wecarried out sand-box analogue experiments, in whichcaldera formation (modeled by evacuation of a rubberballoon) was simulated. The deformation of volcaniccones was studied by placing sand-cones in the vicinity ofthe expected “caldera” rim. At the initial stage of themodeled subsidence, the propagating ring fault of thecaldera bifurcates within the affected cone into two faults,the outermost of which is notably curved outward off thecaldera center. The two faults dissect the cone into threeparts: (1) a stable outer part, (2) a highly unstable andsubsiding intracaldera part, and (3) a subsiding grabenstructure between parts (1) and (2). Further progression ofthe caldera subsidence is likely to cause failure of parts(2) and (3) with failed material sliding into the calderabasin and with formation of an amphitheater-like de-pression oriented toward the developing caldera. Themass of material which is liable to slide into the calderabasin, and the shape of the resulted amphitheater are afunction of the relative position of the caldera ring faultand the base of the cone. A cone situated mostly outsidethe ring fault is affected to a minor degree by calderasubsidence and collapses with formation of a narrowamphitheater deeply incised into the cone, having a smallopening angle. Accordingly, the caldera exhibits aprominent outward embayment. By contrast, collapse of acone initially situated mostly inside the caldera results ina broad amphitheater with a large opening angle, i.e. theembayment of the caldera rim is negligible. The rela-tionships between the relative position of an edifice abovethe caldera fault and the opening angle of the formedamphitheater are similar for the modeled and the naturalcases of caldera/cone interactions. Thus, our experimentssupport the hypothesis that volcanic edifices affected bycaldera subsidence can experience large-scale failureswith formation of indicative amphitheaters oriented to-ward the caldera basins. More generally, the scallopedappearance of boundaries of calderas in contact with pre-caldera topographic highs can be explained by the grav-itational influence of topography on the process of calderaformation.
Keywords: 38.37.25 Вулканология; Caldera subsidence; Volcano instability; Large-scale landslides; Debris avalanche